Internet Search Engines: A Comparative Study and Evaluation Methodology - Biradar, B. S.; Sampath Kumar, B. T. (Journal of Information and Knowledge, 2006)
Paper reports on the evaluation of six search engines viz., Yahoo, Google, Altavista, Lycos, Excite and Hotbot. The findings indicate that search results of each of the search engines vary significantly from one another. It is found that Altavista searched more number of sites (45,448) while Excite searched least number of sites (283). In case of relevancy of search engines majority of relevant sites were found in case of Google (28%) followed by Yahoo (26%) and Altavista (20%). Further analysis shows that more number of irrelevant sites found in case of Hotbot (61.6%), Lycos (59.6%) and Alatavista (54.8%).